Looking Deep into the Eye-of-the-Tiger in Pantothenate Kinase–Associated Neurodegeneration - Lee, J.-H.; Gregory, A.; Hogarth, P.; Rogers, C.; Hayflick, S.J. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: A detailed delineation of the MR imaging changes in the globus pallidus in pantothenate kinase–associated neurodegeneration will be helpful for diagnosis and monitoring of patients. The aim of this study was to determine the morphologic spectrum of the “eye-of-the-tiger” sign and the topographic pattern of iron deposition in a group of patients with pantothenate kinase–associated neurodegeneration.MATERIALS AND METHODS: Seventy-four MR imaging scans from 54 individuals with PANK2 mutations were analyzed for signal patterns in the globus pallidus. Sixteen SWI data from 15 patients who underwent 1.5T (n = 7), 3T (n = 7), and 7T (n = 2) MR imaging were included to visualize the iron topography.RESULTS: The linear hyperintensity alongside the medial border of the globus pallidus was the earliest T2 signal change. This finding was evident before SWI changes from iron deposition became visible. T2WI performed in early childhood mostly showed isolated hyperintense signal. In adult patients, marked signal reduction within an earlier hyperintense center resulting from iron accumulation led to the loss of signal difference between the central and surrounding areas. Signal hypointensity on SWI progressed from the medial to the lateral portion of the globus pallidus with increasing age. The fiber connections between the medial globus pallidus and the anteromedial aspect of the substantia nigra and subthalamic nucleus were markedly hypointense on SWI.CONCLUSIONS: In pantothenate kinase–associated neurodegeneration, the globus pallidus MR imaging changes using SWI develop as region-specific and age-dependent phenomena. Signal inhomogeneity was observed across the globus pallidus in pantothenate kinase–associated neurodegeneration and should be considered when determining the concentration of iron.PKANpantothenate kinase–associated neurodegenerationGPglobus pallidusSNsubstantia nigraSTNsubthalamic nucleus